Kennis of wysheid vir verpleegkunde? - A. Botes (AOSIS, 1998)
Nursing Science is the knowledge content for nursing. The goal of nursing is to promote, maintain and restore people's health. To provide for the health needs of the South African society Nursing Science must generate the right kind of knowledge. The question of the article is whether Nursing Science needs knowledge or wisdom? The perpectives on knowledge of Maxwell (1988) and Rossouw (1993) are studied. The conclusion is that Nursing Science needs knowledge and wisdom. Arguments are given to support this conclusion.